2016
DOI: 10.1016/j.ceramint.2016.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SiC whiskers and graphene nanosheets on the mechanical properties of ZrB2-SiCw-Graphene ceramic composites

Abstract: a b s t r a c tUltrahigh temperature ZrB 2 -SiC w -Graphene ceramic composites are fabricated by hot pressing ZrB 2 -SiC w -Graphene oxide powders at 1950°C and 30 MPa for 1 h. The microstructures of the composites are characterized by Scanning electron microscopy, Raman spectroscopy and X-ray diffraction. The results show that multilayer graphene nanosheets are achieved by thermal reduction of graphene oxide during sintering process. Compared with monolithic ZrB 2 materials, flexural strength and fracture tou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Ongoing studies have confirmed that the introduction of silicon carbide or refractory metal silicide into the composition of UHTCs based on ZrB 2 (HfB 2 ) supports a significant increase in their resistance to oxidation at temperatures >1800-2000 • C, including under the influence of high-speed gas flows containing atomic oxygen (which is characteristic of aerodynamic heating by supersonic/hypersonic air flows) while maintaining increased thermal conductivity [16,[25][26][27][28][29][30][31][32][33]. Modification of these ceramic materials with carbon materials (graphite, carbon fibers or carbon nanotubes), as shown in [34][35][36][37][38][39][40][41], makes it possible to slightly improve crack resistance and thermal shock resistance. In our previous studies, it was established [42][43][44] that due to the introduction of a small amount (1-2 vol.%) of graphene into the composition of HfB 2 -30 vol.%SiC material, there is an opportunity to reduce the degree of its degradation (thickness of the oxidized layer and rate of entrainment) by reducing the temperature that is reached at the surface under the same thermochemical effect of supersonic dissociated air flow, which is probably due to the increase in thermal conductivity.…”
Section: Introductionmentioning
confidence: 94%
“…Ongoing studies have confirmed that the introduction of silicon carbide or refractory metal silicide into the composition of UHTCs based on ZrB 2 (HfB 2 ) supports a significant increase in their resistance to oxidation at temperatures >1800-2000 • C, including under the influence of high-speed gas flows containing atomic oxygen (which is characteristic of aerodynamic heating by supersonic/hypersonic air flows) while maintaining increased thermal conductivity [16,[25][26][27][28][29][30][31][32][33]. Modification of these ceramic materials with carbon materials (graphite, carbon fibers or carbon nanotubes), as shown in [34][35][36][37][38][39][40][41], makes it possible to slightly improve crack resistance and thermal shock resistance. In our previous studies, it was established [42][43][44] that due to the introduction of a small amount (1-2 vol.%) of graphene into the composition of HfB 2 -30 vol.%SiC material, there is an opportunity to reduce the degree of its degradation (thickness of the oxidized layer and rate of entrainment) by reducing the temperature that is reached at the surface under the same thermochemical effect of supersonic dissociated air flow, which is probably due to the increase in thermal conductivity.…”
Section: Introductionmentioning
confidence: 94%
“…Graphene-reinforced ceramic composites, which possess the strongest 2D nanomaterial, have been studied extensively [161][162][163][164][165][166][167][168][169][170]. Two reviews have already examined critically the effect of graphene [171,172].…”
Section: Strengthmentioning
confidence: 99%
“…For bionic layered graphene ceramic matrix composites, little research has been conducted on the grinding and removal mechanisms, crack propagation mechanisms, process parameter optimization and surface and subsurface damage mechanisms. However, the structure of composites is a layered biomimetic structure, referencing the "brick-bridge-mud" crossscale micro and nano structure of a shell [21] , and this highly ordered structure provides the composite with better properties than any single component, which is different from the fiber bundle structures of fiber toughened ceramic matrix composites, and the grinding theories on hard and brittle materials and fiber toughened composites are insufficient to explain the grinding process of the composites. Moreover, with the gradual application of bionic layered graphene ceramic matrix composites, there will be more and more processing problems about this material, which will affect the promotion of this ceramic material.…”
Section: Introductionmentioning
confidence: 99%